(x² + 2√xy) = 5/4
2y - √2xy = 0
From the first equation
(2x-1)²+8√2xy=4
Expand the bracket
(2x-1) (2x+ 1) + 8√2xy = 4
4x² + 2x -2x - 1 + 8√2xy = 4
4x² - 1 + 8√2xy = 4
Collect like terms
4x² + 8√2xy = 4 + 1
4x² + 8√2xy = 5
Find the common factor
4(x² + 2√xy) = 5
(x² + 2√xy) = [tex]\frac{5}{4}[/tex]
For equation 2, we have
4y-√8xy-1=1
4y - [tex]\sqrt{4 *2 xy }[/tex] = 1 -1
4y - [tex]2\sqrt{2xy}[/tex] = 0
Find the common factor
[tex]2(2y - 2\sqrt{2xy} ) = 0[/tex]
[tex]2y - 2\sqrt{2xy} = 0[/tex] × 2
[tex]2y - \sqrt{2xy} = 0[/tex]
Learn more about algebraic expression here:
https://brainly.com/question/723406
#SPJ1